CD4 cell count recovery in HIV/TB co-infected patients versus TB uninfected HIV patients - Wanchu A; Kuttiatt V; Sharma A; Singh S; Varma S (Wolters Kluwer Medknow Publications, 2010)
Background: There is lack of data comparing the improvement in CD4 count following antitubercular (ATT) and antiretroviral therapy (ART) in patients presenting with Human Immunodeficiency Virus/Tuberculosis (HIV/TB) dual infection compared with CD4 matched cohort of TB uninfected HIV patients initiated on ART. We sought to test the hypothesis; TB additionally contributes to reduction in CD4 count in HIV/TB co-infected patients and this would result in greater improvement in count following treatment compared with CD4 matched TB uninfected individuals. Materials and Methods: In a retrospective cohort study design we studied the change in CD4 cell counts in two groups of patients - those with CD4 cell count >100 cells / mm 3 (Group 1) and <100/mm 3 (Group 2) at presentation. In each group the change in CD4 cell count in dually infected patients following six-month ATT and ART was compared to cohorts of CD4 matched TB uninfected patients initiated on ART. Results: In Group 1 (52 patients) dually infected subjects′ CD4 count improved from 150 cells/ mm 3 to 345 cells/mm 3 (P=0.001). In the control TB uninfected patients, the change was from 159 cells/mm 3 to 317 cells/mm 3 (P=0.001). Additional improvement in dually infected patients compared to the control group was not statistically significant (P=0.24). In Group 2 (65 patients) dually infected subjects count improved from 49 cells/mm3 to 249 cells/mm 3 (P=0.001) where as in control TB uninfected patients improvement was from 50 cells/ mm 3 to 205 cells/mm 3 (P=0.001), there being statistically significant additional improvement in dually infected subjects (P=0.01). Conclusion: Greater increment in CD4 counts with ATT and ART in dually infected patients suggests that TB additionally influences the reduction of CD4 counts in HIV patients.